2021
DOI: 10.1039/d1sm01109j
|View full text |Cite
|
Sign up to set email alerts
|

Pressure–deformation relations of elasto-capillary drops (droploons) on capillaries

Abstract: An increasing number of multi-phase systems exploit complex interfaces with interfacial stresses of multiple origins. Despite growing efforts, simple and reliable experimental characterisation of the interfacial properties remains a challenge,...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 48 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…In general, the stress state of the evolving inhomogeneous membrane of such a capsule is very complex and depends on the mechanical properties of the membrane, the time-and radius-dependent stress tensor of such thick membranes, 51 the initial, stress-free state, and the mechanical connection to the needle. 52 Therefore, an accurate evaluation of the membrane elastic modulus is not possible. However, the existence of the elastic properties of the capsule can be tested in our setup shown in Figure 1 by changing the capsule volume and measuring the corresponding pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the stress state of the evolving inhomogeneous membrane of such a capsule is very complex and depends on the mechanical properties of the membrane, the time-and radius-dependent stress tensor of such thick membranes, 51 the initial, stress-free state, and the mechanical connection to the needle. 52 Therefore, an accurate evaluation of the membrane elastic modulus is not possible. However, the existence of the elastic properties of the capsule can be tested in our setup shown in Figure 1 by changing the capsule volume and measuring the corresponding pressure changes.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed follow-up of the bubble growth kinetics using a high-speed camera in the limit where it is limited by the interfacial rheology, seems a promising prospect for this work, since it could open the way to a new characterization of the interfacial rheology of surfactants in a nearly spherical geometry. Indeed, it has been recently shown that "Capillary pressure Elastometry", which consists in analyzing the quasi-static pressure-deformation curves for a bubble in this type of geometry, allows to analyse the elastic properties of interfaces [35]. The simple model proposed here should allow to extend the field of application of "Capillary pressure Elastometry" to the dynamic response of interfaces.…”
Section: Discussionmentioning
confidence: 99%
“…The transition to solid elasticity then gives rise to deviatoric anisotropic stresses, which can no longer be taken into account as an effective isotropic and homogeneous surface tension γ eff obtained by solving the usual Young–Laplace equation. 17,27,29–33,41–44…”
Section: Methodsmentioning
confidence: 99%
“…The dilational investigations are performed combining shape analysis and pressure measurements 27 of a bubble held by a needle in solution during sinusoidal or linear volume changes. The dilational response of the interface being rapidly non-linear, we apply for the first time the method of general stress decomposition (GSD) [28][29][30] to polyelectrolyte multilayers.…”
Section: Introductionmentioning
confidence: 99%